APPLICATION OF LINEAR PROGRAMMING FOR DORMITORY DEVELOPMENT PLAN AT PETRA CHRISTIAN UNIVERSITY - Connie Susilawati (Civil Engineering Dimension, 2001)
Dormitory is a very important facility which have to be provided by a university. A survey to Petra Christian University’s students has been conducted to understand the required facilities and their financial ability. Linear programming has been used to calculate number of rooms and area of each facility which could satisfy the constraints and to obtain optimum profit. Number of bedrooms, number of bathrooms, and area of each facility, such as: living room, dining room, common room, cafeteria, book shop, mini market, phone booths, sport facilities, and parking space are recommended. Since the investment is financially feasible, the dormitory could be built in the future.